ANALYSIS OF THE WAIST-HEIGHT INDEX AND OF THE CENTRALIZED FAT MEASURED FOR ABSORPTIOMETRY X-RAY OF DUAL-ENERGY (Fiep Bulletin - online, 2013)
This study had as objective to analyze the waist-height index (WHI) with the total fat and centralized measured by the absorptiometry x-ray of dual-energy (AXDE), and also identifying the prevalence of health risk associated with WHI. It is a study correlational descriptive and 45 young men with age between 20 and 30 years, participated in the study. The variables in study were total body mass (kg), stature (cm), circumference of the waist (CW), percentage of total fat (%G ) and percentage of fat of the trunk TOTAL (%G ) measured by AXDE and WHI. To verify the relationship between the WHI and %G and %G , the lineal correlation of TRUNK TOTAL TRUNK Pearson (p>0, 01) was used as well as the analysis of simple lineal regression, being calculated later the test t of Student, the deterministic index (R2) and the constant error (CE). The results demonstrated a strong correlation between WHI and %G (r=0, 89; TOTAL p
Keywords: Waist-height index; centralized fat; absorptiometry x-ray of dual-energy